Predictors of Failed Trial of Labour After Previous one Caesarean Section - Mahreen, Anam; Viqar Ashraf; Rabia Sajjad; Naheed Hayat (Pakistan Armed Forces Medical Journal, 2023)
OBJECTIVE To look for failed trail of labour after one caesarean section and predicting factors associated with failed labour STUDY DESIGN Comparative Cross-sectional Study SETTING AND DURATION OF STUDY Gynaecology and Obstetrics department Pak Emirates Military Hospital Rawalpindi. From May 2021 to October 2021. METHODS A prospective study was conducted on the women who were booked cases in our department for antenatal checkups and labour. Those women with history of one caesarean section were recruited for the analysis. They underwent labour in our department and those with failed labour were diagnosed and managed by consultant obstetrician. Relevant clinical factors associated with failed labour among women with one previous caesarean section included in our study. RESULTS A total of 380 women who underwent labour in our hospital with one previous caesarean section were recruited. Mean age of the women included in the study was 34.435±7.361 years. 162 (42.6%) had successful trial of labour while in 218 (57.4%) women trail of labour could not succeed. Statistical analysis revealed that gestation age more than 40 weeks, poor Bishop score (<5) at admission and requirement of labour augmentation (with oxytocin) were found statistically significantly associated with failed trial of labour in our study participants (p-value<0.05). CONCLUSION Failed trial of labour was a common clinical condition in women with one previous caesarean section. Women with gestation age more than 40 weeks, poor bishop score at admission and requiring labour augmentation were more at risk of having failed trial in our study participants.